Acoustic Absorption Coefficient of Oil Palm Midrib Composite - Defrianto Defrianto; Muhammad Ahlunnazah; Saktioto Saktioto; Nuraina Fika Lubis (Lambung Mangkurat University Press, 2025)
Composite from oil palm midrib waste is one of the natural fiber materials that can reduce noise. Its material sample composite with gypsum was placed inside an impedance tube, which fitted with the mass of palm midrib mill, i.e., 0.1 kg, 0.15 kg, and 0.2 kg. Next, sound absorption coefficients were measured based on the two farthest ranges of the sound-receiving microphone, i.e., range A, which was 45 cm from the sample, and range B, which was 55 cm from the sample. Sound source frequencies were used, i.e., 125 Hz, 250 Hz, 500 Hz, 1000 Hz, and 2000 Hz. This research found that the link between sound absorption coefficients and the mass differences of each sample was not significantly affected. The highest sound absorption coefficient is 0.979 in distance A for oil palm midrib sample mass of 0.15 kg, far bigger than gypsums on the same frequency (125 Hz), which is 0.29. In conclusion, sound absorption on oil palm midrib was better because it has higher sound absorption coefficients than gypsum and a minimum sound absorption coefficient standard of 0.15. In the future, oil palm midribs might be widely used as sound-absorbing materials based on their advantages.